Green economy: Private sectors’ response to climate change - Ansah, Richard Hannis; Sorooshian, Shahryar (John Wiley and Sons Inc., 2019)
The focus of this paper is to present a discussion of the role of the private sector in response to the need for climate change adaptations. The study, which was conducted through a literature review, investigates the concept of the green economy and climate change, as well as businesses’ commitment to advance climate actions in ways that build resilience in vulnerable communities in developing countries. The paper calls on companies with national, regional, and/or global reach to adopt or develop strategies that improve resource efficiency, reduce greenhouse gas emissions, and reduce the loss of biodiversity. Businesses can accelerate this transition by aligning their investments with climate change adaptation opportunities, and thus, “green” the economy. In addition, green growth could be achieved through tactical public and private investments in mitigating climate change. The paper concludes that the private sector is a key sector in addressing the challenges of vulnerable communities, and it has much to contribute to the planning, development, and implementation of climate adaptation strategies, including sector-specific expertise, technology, efficiency, financing, and entrepreneurship. Finally, some social conditions and environmental boundaries have been highlighted in this paper to attract the attention of business leaders who are trying to build initiatives and advance climate actions that will reduce socio-community risks from climate change. Also, comprehensive initiatives and strategies have been recommended to private companies seeking to address climate vulnerabilities.